W/O/W type lotion formulation of “arum manis” mango (Mangifera indica L.) pell as antioxidant - Widya Rudiana; Wulandari Wulandari; Lilies Wahyu Ariyani (Journal of Health Management and Pharmacy Exploration, 2023)
Arum manis mango peel contains compounds, namely flavonoids. Flavonoid compounds act as natural antioxidants. The weakness of flavonoid compounds is that they are not stable to the influence of high temperature and light intensity, so that the arum manis mango peel extract is made in the form of lotion type W/O/W. This study aims to determine the physical characteristics and stability of the W/O/W type emulsion form optimum formula in double emulsion preparations and lotion preparations, determine the stability of W/O/W type lotion preparations during storage using the cycling test method and determine the IC50 value in the optimum formula. lotion preparation type W/O/W. The optimum formula for double emulsion type W/O/W is found in formula 5 with a ratio of primary emulsion: secondary emulsion (80%:20%) with span 80 (10%) and tween 20 (5%) concentrations while the optimum formula for lotion preparations found in formula 3 with a ratio of double emulsion type W/O/W: lotion base (80%:20%) with a concentration of stearic acid (5%), cetyl alcohol (2.5%) and glycerin (10%). In the antioxidant activity of lotion preparations, the IC50 value was 136.543 ppm and the stability test on the cycling test method had an unstable form.